DIAKONIA SEBUAH KONSEP DAN PRAKSIS YURIDIS PASTORAL - uilkpastoral, juilkpastoral; Benteng Kurniadi, Benediktus (IN VERITATE LUX, 2018)
The term "diakonia" is commonly used in the context of ecclesiology because it is one of the foundations and directions of the Church's mission in the world, participating in the universal mission of Christ, which is salvation. Diakonia is the tangible movement of the Church in embodying God's love for the world, allowing the world to increasingly know Him, "love your fellow human beings as I have loved you," a love based on the love of Christ himself. Through diakonia, the Church is expected to lead people to an awareness of the greatness of God's love for humanity through acts of loving service expressed in various contextual ways and forms, adhering to the principle of "Ecclesia semper reformanda est." In the ecclesiological and pastoral canonical perspective, a deacon in the ecclesiastical ministry not only participates in the "mensa" of the Eucharist but also directly engages in charitable services, such as serving the poor, administering sacraments permitted according to the norms of the Church, and more. Diakonia in the ecclesiological and pastoral perspective is not fundamentally different but rather a complete unity, as its foundation and purpose are the same, only within the hierarchical framework (status and function) is it refined and detailed. All of these functions operate within the framework of "salus animarum" or the salvation of souls. In this written work, the hierarchical aspect of diakonia is emphasized, even though it also explores diakonia from an ecclesiological (theological) perspective